Early onset cerebellar ataxia with retained tendon reflexes: a clinical and genetic study of a disorder distinct from Friedreich's ataxia. Issue 6 (June 1981) - Harding, A E
Abstract : Twenty patients are described with a distinctive clinical syndrome characterised by progressive cerebellar ataxia developing within the first two decades. This is associated with dysarthria, pyramidal signs in the limbs, normal or increased knee jerks and upper limb reflexes and in some instances sensory loss. Inheritance is probably autosomal recessive in the majority, if not all, of the cases. The preservation of tendon reflexes distinguishes this disorder from Friedreich's ataxia. Other important differences from Friedreich's ataxia are absence of optic atrophy, cardiomyopathy, diabetes mellitus and severe skeletal deformity. The prognosis was better in the present series than in cases of Friedreich's ataxia; patients remained ambulant, on average, for more than 10 years longer.